2022
DOI: 10.1111/liv.15457
|View full text |Cite
|
Sign up to set email alerts
|

Human poliovirus receptor contributes to biliary atresia pathogenesis by exacerbating natural‐killer‐cell‐mediated bile duct injury

Abstract: Background and Aims Natural killer (NK) cells play an important role in biliary atresia (BA) pathogenesis; human poliovirus receptor (PVR) is an important NK‐cell modulator. Here, we explored the role of PVR in BA pathogenesis. Methods Poliovirus receptor expression and NK cell‐associated genes were detected in human BA samples and a rotavirus‐induced BA mouse model using quantitative PCR and immunofluorescence staining. Chemically modified small interfering RNA silenced PVR expression in the BA model, and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Furthermore, PVR may be involved in the pathogenesis of BA by regulating the NK cell-mediated bile duct injury. 99 Besides, the concentration of PVR in the sera of children with BA was significantly higher than that in the sera of healthy controls. This suggests that PVR may be a potential biomarker of BA.…”
Section: Other Potential Biomarkersmentioning
confidence: 90%
See 2 more Smart Citations
“…Furthermore, PVR may be involved in the pathogenesis of BA by regulating the NK cell-mediated bile duct injury. 99 Besides, the concentration of PVR in the sera of children with BA was significantly higher than that in the sera of healthy controls. This suggests that PVR may be a potential biomarker of BA.…”
Section: Other Potential Biomarkersmentioning
confidence: 90%
“…Biomarkers that can be used to diagnose BA have always been the focus of attention. Li et al 99 found that human poliovirus receptor (PVR) expression was upregulated in the bile ducts of patients with BA and RRV-induced BA mice. Furthermore, PVR may be involved in the pathogenesis of BA by regulating the NK cell-mediated bile duct injury.…”
Section: Other Potential Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation